I Am Juan Pedro, Case Study of the Gambler’s Script Adapted By Rachman Sabur - Simanjuntak, Robinsar H.; Bayumie, M.A.T. (Indonesian Research Journal on Education, 2025)
Theatrical performances are collective work of various parties. Actors play characters based on the interpretation of the play script. This research is important because it focuses on the current situation, where many changes have affected the results, particularly the different time and place conditions. The Gamblers tells the story of a skilled gambler, who always wins in his game. The method used in this study is descriptive qualitative. The character Pedro is analyzed in detail in the script. Observation of the character Pedro by searching for model examples and aligning all aspects, including the setting of the place, time, placement of characters and background so that they are in accordance with real life today. The author watched the documentation of The Gamblers script on YouTube, watched live theater performances and several films. The results of this study indicate that the main character in this script is Pedro, a clever person with a Spanish accent. The Gamblers consists of one act. Tells about fraud, cheating, and the struggle for wealth packaged using comedy elements.